2020
DOI: 10.1016/j.ijid.2020.08.060
|View full text |Cite
|
Sign up to set email alerts
|

A call for strengthened evidence on targeted, non-pharmaceutical interventions against COVID-19 for the protection of vulnerable individuals in sub-Saharan Africa

Abstract: Highlights Curbing the transmission of SARS-CoV-2, the causative agent of COVID-19, may be difficult in sub-Saharan Africa. Overall COVID-19-related mortality remains low because of the young population. Protecting vulnerable individuals from severe disease should be a priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
0
10
1
Order By: Relevance
“…The second, the topics and references. Category Topic and references Change to medical practice Mental health care [254] , [257] , [261] , [273] , [274] , [275] ; Emergency care [276] , [277] ; Substance abuse [253] , [263] , [278] , [279] , [280] ; Oncological care [264] , [281] Health care practices [255] , [259] , [262] , [282] , [283] , [284] ; Pediatric care [283] , [285] Other care [256] , [260] , [268] , [286] , [287] , [288] Modeling Modeling approaches [28] , [265] , [289] , [290] , [291] , [292] , [293] ; Transmission dynamics [294] , [295] , [296] , [297] , [298] Mobile phone data [29] ; estimation [258] Effect of NPIs Effects on: children ...…”
Section: Comments And/or Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The second, the topics and references. Category Topic and references Change to medical practice Mental health care [254] , [257] , [261] , [273] , [274] , [275] ; Emergency care [276] , [277] ; Substance abuse [253] , [263] , [278] , [279] , [280] ; Oncological care [264] , [281] Health care practices [255] , [259] , [262] , [282] , [283] , [284] ; Pediatric care [283] , [285] Other care [256] , [260] , [268] , [286] , [287] , [288] Modeling Modeling approaches [28] , [265] , [289] , [290] , [291] , [292] , [293] ; Transmission dynamics [294] , [295] , [296] , [297] , [298] Mobile phone data [29] ; estimation [258] Effect of NPIs Effects on: children ...…”
Section: Comments And/or Perspectivesmentioning
confidence: 99%
“…Several comments and/or perspectives focus on different aspects of modeling COVID-19 dynamics and NPIs. In particular, we find articles discussing epidemic modeling efforts [28] , [265] , [289] , [290] , [291] , [292] , [293] , analyzing knowns and unknowns of transmission dynamics [294] , [295] , [296] , [297] , [298] , presenting opportunities to model and control the spreading of COVID-19 enabled by novel data streams such as mobile phone data [29] , and discussing the challenges in estimation [258] .…”
Section: Comments And/or Perspectivesmentioning
confidence: 99%
“…It has been recently suggested that locally implemented COVID-19 preventive strategies could potentially explain, at least in part, the as yet slow spread of COVID-19 in SSA. 8 9 The present study collected data which could shed some more light on this issue. In our ongoing longitudinal study, preventive behaviours cover individual protection measures by the study’s participants and collective prevention strategies implemented by administrative, religious or medical authorities in the area covered by the survey.…”
Section: Methods and Analysismentioning
confidence: 98%
“…Recently, another strong hypothesis has been put forward, suggesting that the extensive implementation of local preventive strategies may have played a crucial role in substantially lowering the spread of the disease. 8 9 …”
Section: Introductionmentioning
confidence: 99%
“…However, extensive research on the effects of the pandemic on these vulnerable populations in West Africa has been limited. Furthermore, even fewer studies have reviewed African countries’ targeted interventions to limit the effects of measures such as lockdowns on vulnerable populations and have examined the effectiveness of such interventions on the wellbeing of vulnerable populations [ 16 , 17 ]. Additionally, based on our findings, not many studies have examined the role that managing the Ebola epidemic has played in a country’s response to managing COVID-19, particularly in efforts to protect vulnerable populations.…”
Section: Introductionmentioning
confidence: 99%